Semantic approaches to place in modern theatre (Journal of the College of Basic Education, 2022)
The problem of research and the need for it based on the necessity of theatrical openness in Iraq on modern methodological approaches and the study of theatrical experiences, schools and modern theories, especially the semiotic approach or the semiotic approach to its essence and not being satisfied with what is in circulation and recognized in terms of sociological, normative, impressionistic and historical approaches despite the role he played and what It is still being performed by critics, researchers, theater directors, designers, and those who are committed to these approaches in their handling of the performances presented by theatrical groups in Iraq.